Pengaruh Penerapan Model Pembelajaran Auditory Intellectualy Repetition (AIR) Terhadap Kemampuan Pemahaman Konsep Matematis Siswa di SMP Muhammadiyah 50 Jakarta - Muhammad Rizki Ramadhan (Jurnal Riset Pendidikan Matematika Jakarta, 2023)
This study aims to determine whether there is a significant effect of applying the structured Auditory Intellectually Repetition (AIR) learning model on students' ability to understand mathematical concepts. This research was conducted on class VII students of SMP Muhammadiyah 50 Jakarta in the odd semester of the 2022/2023 school year on numbers. The research method used is a quasi-experimental design (pseudo-experiment). Sampling using cluster random sampling technique, namely the random selection of two classes that are normally distributed, homogeneous, and have the same mean. The sample selected in this study was class VII-1 as the experimental class and class VII-2 as the control class. The research instrument used was a test of the ability to understand students' mathematical concepts in the matter of numbers as many as seven essay questions. Based on the calculation of the research data, the data for both classes come from populations that are normally distributed and have the same or homogeneous variance. Therefore, statistical hypothesis testing was carried out using the t-test with the same variance. Based on the results of testing the hypothesis, the value of which means reject H_0 at the significance level